High expression of COPZ2 is associated with poor prognosis and cancer progression in glioma - Geng, Zhi; Mu, Chunyan; Qiu, Yuxiang; Tang, Yuchen; Su, Mingyu; Tang, Chuanxi; Zhang, Lei (Frontiers in Molecular Neuroscience, 2024)
BackgroundCoatomer protein complex zeta 2 (COPZ2) is a member of heptameric coatomer protein complex I and has been reported to be involved in various tumors. However, COPZ2’s potential involvement in glioma remains to be explored.MethodsThe COPZ2 expression and related clinical data were obtained from The Cancer Genome Atlas (TCGA). TIMER2.0 and the Ualcan database were utilized to assess the COPZ2 expression in various tumors. Univariable, multivariate Cox regression, Kaplan–Meier methods, nomogram analysis, and ROC curve analysis were carried out to assess the relationship of COPZ2 and other prognostic factors with glioma. The LinkedOmics database was used to predict the potential biological mechanism of COPZ2 in glioma. We also conducted in vitro experiments to evaluate the functional role and mechanism of COPZ2 in glioma cell lines.ResultsWe found that COPZ2 was highly expressed in glioma and it was associated with age and WHO grades. Kaplan–Meier survival curves, Cox analysis, nomogram analysis, and ROC curve showed that COPZ2 was a disadvantageous factor in poor glioma prognosis. The functions of COPZ2 and co-expression genes were significantly associated with neutrophil-mediated immunity, granulocyte activation, and response to interferon-gamma. In addition, COPZ2 knockdown significantly inhibited the proliferation, migration, and invasion of glioblastoma cells. Mechanistically, COPZ2 suppressed tumor development by participating in the regulation of the PI3K-AKT signaling pathway.ConclusionOur results demonstrated that the elevation of COPZ2 was associated with the prognosis and progression of glioma, and it might be a potential diagnostic and prognostic biomarker for glioma.